Synthesis and Structural Analysis of Chiral Bis-dihydro[1,3]-naphthoxazines and Imidazolidine Derivatives Prepared by Three-Component Mannich-Type Condensation - Maya Tavlinova-Kirilova; Krasimira Dikova; Maya K. Marinova; Mariana Kamenova-Nacheva; Rusi Rusew; Hristina Sbirkova-Dimitrova; Boris Shivachev; Kalina Kostova; Vladimir Dimitrov (Crystals, 2023)
Enantiomerically pure (S)-1-phenylethan-1-amine has been applied in Mannich-type condensation between formaldehyde and naphthalenediols leading to the synthesis of chiral bis-dihydro[1,3]naphthoxazines in excellent yields. Salen-type structures have been synthesized, applying R,R- or S,S-cyclohexane-1,2-diamines in condensation with formaldehyde and naphthalene-2-ol. The obtained chiral imidazolidine derivatives of the type 1,1′-(((3a,7a)-hexahydro-1H-benzo[d]imidazole-1,3(2H)diyl)bis(methylene))bis(naphthalen-2-ol) were evaluated as pre-catalysts for the addition of diethyl zinc to aldehydes. The structures of the newly synthesized compounds were elucidated using 1D and 2D NMR experiments (COSY, HMBC, HSQS), elemental analysis, mass spectrometry (HRMS spectra) and single-crystal X-ray diffraction (SCXRD). The products were further characterized with powder X-ray diffraction (PXRD) and thermal analysis (DSC).